Strategic applications of long-acting acaricides against Rhipicephalus (Boophilus) microplus in northwestern Argentina, with an analysis of tick distribution among cattle - Nava, Santiago; Mangold, Atilio Jose; Canevari, Jose Tobias; Guglielmone, Alberto (2018)
Strategic applications of long-acting acaricides for the control of Rhipicephalus (Boophilus) microplus in northwestern Argentina were evaluated for one year. In addition, tick distribution among cattle was analyzed to evaluate if partial selective treatment or culling the small proportion of most heavily infested animals were feasible options to control R. (B.) microplus. Two different treatments schemes based on two applications of fluazuron and one application of 3.15% ivermectin were performed. Treatments were made in late winter and spring so as to act on the small 1st spring generation of R. (B.) microplus, in order to preclude the rise of the larger autumn generation. The overall treatment effect was positively significant in both schemes. The number of ticks observed in the control group was significantly higher than in the treated groups on all post-treatment counts. Group 2 exhibited more than 80% of efficacy almost throughout the study period, whereas Group 1 exhibited an efficacy percentage higher than 80% in September, October, December, February, April and May, but not in November (73.4%), January (58.3%), March (45.2%) or June (53.4%). Absolute control was observed in Group 2 in the counts of September and October, and in Group 1 in the count of February. The control strategies evaluated in this work provide an acceptable control level with only three applications of acaricides; at the same time, they prevent the occurrence of the autumn peak of tick burdens, which is characteristic of R. (B.) microplus in northwestern Argentina. Tick distribution was markedly aggregated in all counts. Although ticks were not distributed evenly among calves, the individual composition of the most heavily infested group was not consistent throughout the study period. In addition, the level of aggregation varied with tick abundance. These results suggest that applying acaricides to a portion of the herd or culling the most infested individuals at a given moment of the year may not be proper methods to achieve a significant control of R. (B.) microplus in northwestern Argentina.